2016
DOI: 10.1186/s12877-016-0202-9
|View full text |Cite|
|
Sign up to set email alerts
|

Gender differences in metabolic syndrome components among the Korean 66-year-old population with metabolic syndrome

Abstract: BackgroundGender is thought to be an important factor in metabolic syndrome and its outcomes. Despite a number of studies that have demonstrated differences in metabolism and its components that are dependent on gender, limited information about gender differences on the characteristics of metabolic syndrome and its components is available regarding the Korean old adult population. This study aimed to identify gender differences in characteristics of the metabolic syndrome and other risk factors for cardiovasc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

7
33
1
3

Year Published

2016
2016
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 56 publications
(44 citation statements)
references
References 36 publications
7
33
1
3
Order By: Relevance
“…The most common metabolic component among longevity subjects in our Zhuang population was inconsistent with studies from other ethnic population [ 17 , 18 ]. For example, studies performed in Korea found that the most common component was high blood sugar levels, followed by elevated triglyceride levels and high blood pressure in males, and that elevated triglyceride levels, followed by high blood sugar levels and high blood pressure in females in a 66-year-old population [ 18 ]. In China, it has been shown that the most common component was elevated blood pressure, followed by central obesity and raised fasting glucose among Chinese aged 60 years or older[ 19 ].…”
Section: Discussioncontrasting
confidence: 88%
“…The most common metabolic component among longevity subjects in our Zhuang population was inconsistent with studies from other ethnic population [ 17 , 18 ]. For example, studies performed in Korea found that the most common component was high blood sugar levels, followed by elevated triglyceride levels and high blood pressure in males, and that elevated triglyceride levels, followed by high blood sugar levels and high blood pressure in females in a 66-year-old population [ 18 ]. In China, it has been shown that the most common component was elevated blood pressure, followed by central obesity and raised fasting glucose among Chinese aged 60 years or older[ 19 ].…”
Section: Discussioncontrasting
confidence: 88%
“…There is no agreement in the literature about the prevalence between sexes. Lee et al 20 found a relationship between MS and sex, confirming that women presented more combinations of MS components than men. The main sex differences observed in their study were as follows: higher prevalence of abdominal obesity and low HDL-C in women than in men and a greater prevalence of high triglycerides level, high blood pressure, and high glucose levels in men than in women.…”
Section: Discussionmentioning
confidence: 91%
“…The prevalence of MetS and its phenotypes differs between men and women [11][12][13] . For example, in the Japanese population, the prevalence of MetS with elevated FPG levels is higher in men than in women [11] .…”
mentioning
confidence: 99%